A study on readiness for change among management staffs in Madetill Event Management Sdn. Bhd., Balakong, Selangor Darul Ehsan / Ani Afiqah Mohd Rizuan - Mohd Rizuan, Ani Afiqah (2014)
The objective in this research is to study on readiness for change among management staffs in Madetill Event Management Sdn. Bhd. (MEMSB), Balakong, Selangor Darul Ehsan. This is carried out through the review of literature and experimental analysis. An important part of this process includes developing measurements of the factor that contribute to readiness for change; appropriateness. management support, self efficacy and personal valence. The study is focused around one types of primary data that is a questionnaire survey administered among management staff at MEMSB. The findings shows that the variables that measure the readiness for change are appropriateness, management support, self-efficacy and personal valence. Among these four variables, appropriateness is the factor that measure staff readiness for change that has most value mean with 3.9333. The results of the finding also help the researcher to identify the main factors that contributes to the staff readiness for change in MEMSB. Appropriateness is the factor that most influential factor with the mean 3.9333. The results of the finding also help the researcher to identify the least influential factor that contribute to readiness for change which is personal valence with the mean 3.6282. Based on the findings, in answering research question 4, the results shows that level of readiness for change was high.